Business process reengineering using process mining - Yılmaz, Yeşim. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
In today’s competitive business world, organizations aim to ensure their position by continuously improving their processes to adapt the rapidly changing environment. However, continuous improvement of processes with the traditional approaches require long and costly processes. With the advances in digitalization, a new approach, process mining has been developed to overcome these challenges by using transactional data in information systems. Process mining aims to discover, monitor and improve processes by acquiring knowledge from the event logs. Within the scope of this study, process mining techniques are analyzed to confirm the role of process mining in process improvement by using real process data of an international company in construction sector. These analyses are performed using two different process mining tools: ProM and Celonis. Moreover, these tools are compared using the framework that is generated for the comparison of process mining tools.
Keywords: Workflow -- Management.; Management -- Data processing.; Data mining.